MODEL-MODEL DAN PENDEKATAN DALAM PENGEMBANGAN KURIKULUM BAHASA ARAB DI LEMBAGA PENDIDIKAN (TEORITIS DAN PRAKTIS) - Dhiauddin, DHIAUDDIN (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2016)
Abstract: Curriculum is a component that determine the educational system. In curriculum development, including Arabic curriculum, there many components many components that must associate one another tho achive the targeted objectives in the curriculum development. In addition, there are some models that may be adopted in the curriculum development like The Administrative Model, The Grass roots Model, Model Beuchamp’s system, The demontrasion model, Taba’s interveted model, Roger’s interpersonal relations model, The systematic action-research model, Emerging Technical Model. These models can adjusted to some approaches like academic subject, humanistic, technology, and so forth. The model of developing Arabic curriculum in Indonesia consists of the administrative model curriculum and skill-based curriculum. Kata Kunci: Pengembangan, Kurikulum, Pendekatan, Model, Bahasa Arab